A high-strength cementitious material for synergistic treatment of multi-source solid waste and its preparation
Through the collaborative utilization of multi -source solid waste materials and the regulation of the activation agent, the alkali -excitement composite inorganic gel material with high mechanical strength is prepared, which solves the problem of high energy consumption and insufficient structural strength in the preparation of traditional materials. The effect of improvement of material intensity and decrease in cost.
Patent Information
- Application Number
- CN202310039446.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-01-12
AI Technical Summary
The preparation materials of existing alkali-excited inorganic gelling materials rely on fly ash and kaolin. The process consumes high energy and requires consumption of non-renewable mineral materials. The material prepared by a single raw material is insufficient in structural strength, making it difficult to meet the synchronization of multiple solid wastes. Efficient consumption and utilization.
By utilizing multi-source solid waste materials, such as fly ash, blast furnace slag, steel slag and silicon slag, combined with the function of activators, the types and proportions of raw materials are controlled to prepare composite inorganic cementitious materials with higher mechanical strength.
The high mechanical strength of alkali-activated composite inorganic cementitious materials has been improved. The maximum unconfined mechanical compressive strength in the early stage can reach 107.5MPa, which is 32.92% higher than that of a single inorganic cementitious material. It also reduces the material preparation cost and is feasible for promotion. sex.
Smart Images

Figure CN116217104B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to but is not limited to the technical field of comprehensive utilization of solid waste, and in particular to but is not limited to a high-strength alkali-activated inorganic gelling material using multi-source solid waste materials as raw materials and its preparation. Background Art
[0002] The basic structure of alkali-activated inorganic cementitious materials is an amorphous three-dimensional network structure generated by the sharing of oxygen atoms between silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons. Due to its special hydrated sodium aluminosilicate structure, its formation mainly depends on ionic bonds. Compared with the van der Waals force that the hydrated calcium silicate structure of traditional Portland cement relies on, alkali-activated inorganic cementitious materials have significant advantages in structural strength, chemical stability, high temperature resistance and durability, and have received widespread attention from researchers around the world.
[0003] Since this material was proposed by German scholars in the 1980s, its preparation raw materials mainly rely on fly ash and kaolin. Kaolin (Al2O3·2SiO2) needs to be calcined to 600℃ to 900℃ for dehydration. The process has high energy consumption and requires the consumption of non-renewable mineral materials. In contrast, the structural strength of alkali-activated materials prepared from fly ash alone is lower than that of kaolin-based materials, and the structural strength advantage is insufficient. Therefore, broadening the preparation raw materials of alkali-activated materials is of great significance for improving the structural strength of materials and reducing the cost of material preparation.
[0004] Solid waste materials come from many sources, and the components of solid waste materials generated by different industries vary significantly. However, most solid waste materials contain a large amount of silicon, aluminum, and oxygen elements, which can provide a skeleton structure for alkali-activated materials and have the potential to be prepared as alkali-activated materials.
[0005] The regional distribution of different industries, the output of related solid waste, and the differences in solid waste components will cause large differences in the final performance of alkali-activated materials and poor quality control stability. This application can deeply regulate the raw material components through the analysis and coordinated utilization of multi-source solid waste components, while improving the final molding strength of the material and ensuring the stability of the raw materials, thereby reducing the sensitivity to solid waste distribution, output and component composition, and improving the quality control stability of the final product, which is of great significance for the large-scale quantitative production of related products. Summary of the invention
[0006] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.
[0007] In view of the above problems, the present application provides a composite inorganic gelling material derived from multi-source solid waste materials and a preparation method thereof. The composite inorganic gelling material with higher mechanical strength is prepared by using fly ash, blast furnace slag, steel slag and silica fume and adjusting the type and proportion of raw materials under the action of an activator.
[0008] The purpose of this application is also to provide a resource utilization method for the simultaneous disposal of multi-source solid waste. The method has a streamlined process flow, low raw material and preparation costs, and the molding materials have application value, thereby realizing the simultaneous and efficient disposal of multiple solid wastes.
[0009] The present application provides a cementitious material, which comprises at least two of fly ash, blast furnace slag, steel slag and silicon slag and an activator;
[0010] The cementitious material comprises, by weight, 0 to 100 parts of fly ash, 0 to 100 parts of blast furnace slag, 0 to 40 parts of steel slag, 0 to 40 parts of silicon slag and 40 to 50 parts of the activator.
[0011] In one embodiment provided in the present application, the cementitious material includes, by weight, 0 to 100 parts of fly ash, 0 to 100 parts of blast furnace slag, 0 to 40 parts of steel slag, 0 to 40 parts of silicon slag and 40 to 50 parts of activator, and the composition of the cementitious material does not include a scheme consisting only of blast furnace slag, silicon slag and steel slag in a weight ratio of 1:1:1.
[0012] In one embodiment provided in the present application, the cementitious material includes, by weight, 50 to 100 parts of fly ash, 50 to 100 parts of blast furnace slag, 10 to 40 parts of steel slag, 10 to 40 parts of silicon slag, 40 to 50 parts of activator, and 5 to 10 parts of deionized water.
[0013] In one embodiment provided in the present application, the particle size of any one or more of the fly ash, the blast furnace slag, the steel slag and the silicon slag is not greater than 75 μm.
[0014] In one embodiment provided in the present application, the silicon dioxide content in the fly ash is ≥43wt.%, the aluminum oxide content is ≥40wt.%, the iron oxide content is ≥5.9wt.%, the calcium oxide content is ≥2.8wt.%, and the magnesium oxide content is ≥0.4wt.%; the remainder can be substances such as phosphorus pentoxide and potassium oxide.
[0015] In one embodiment provided in the present application, the fly ash is fine ash collected from flue gas in a coal-burning process in a thermal power plant, and is dried at 70° C. and then collected through a sieve.
[0016] In one embodiment provided in the present application, the silicon dioxide content in the steel slag is ≥11.6wt.%, the aluminum oxide content is ≥4.1wt.%, the iron oxide content is ≥20.0wt.%, the calcium oxide content is ≥48.4wt.%, and the magnesium oxide content is ≥3.6wt.%; the remainder can be sodium oxide, titanium dioxide, phosphorus pentoxide, potassium oxide and other substances.
[0017] The steel slag is waste slag produced in the steelmaking process, which is dried at 70° C. and then ground and sieved for collection.
[0018] In one embodiment provided in the present application, the silicon dioxide content in the silicon slag is ≥ 97.5wt.%; the remainder may be aluminum oxide, calcium oxide, iron oxide, magnesium oxide and other substances.
[0019] The silicon slag is waste slag generated in the process of silicon ore refining, which is dried at 70° C. and then sieved and collected.
[0020] In one embodiment provided in the present application, the silicon dioxide content in the blast furnace slag is ≥21.6wt.%, the aluminum oxide content is ≥11.4wt.%, the iron oxide content is ≥0.6wt.%, the calcium oxide content is ≥55.6wt.%, and the magnesium oxide content is ≥5.8wt.%, and the remainder is iron oxide, titanium dioxide, potassium oxide and other substances.
[0021] The blast furnace slag is a by-product produced in the steelmaking process, which is dried at 70° C. and then ground and sieved for collection.
[0022] In one embodiment provided in the present application, the activator includes a hydrated silicate solution and a strong base.
[0023] In one embodiment provided in the present application, the modulus of the hydrated silicate solution is 3.3 to 3.8.
[0024] In one embodiment provided in the present application, the strong base is selected from sodium hydroxide. In one embodiment provided in the present application, the molar concentration ratio of Na2O / SiO2 in the activator is 0.667.
[0025] In another aspect, the present application provides a method for preparing the above-mentioned gelling material, the method comprising:
[0026] Evenly mixing two, three or four of the fly ash, blast furnace slag, steel slag and silicon slag to obtain a composite solid raw material;
[0027] The composite solid raw material, the activator and water are mixed evenly to obtain the gelling material slurry.
[0028] In one embodiment provided in the present application, the mixing rate of two, three or four of the fly ash, the blast furnace slag, the steel slag and the silicon slag is 100 r / min to 200 r / min, and the mixing time is 5 min to 7 min.
[0029] In one embodiment provided in the present application, the activator is selected from an alkaline activator, and the hydrated silicate solution and the strong base are uniformly mixed to prepare a clear and transparent activator.
[0030] In one embodiment provided in the present application, the activator is subjected to ultrasonic oscillation treatment before use; in one embodiment provided in the present application, the power of the ultrasound is 400W to 500W; in one embodiment provided in the present application, the frequency of the ultrasound is 40kHz; optionally, the time of the ultrasound is 3min to 5min.
[0031] In another aspect, the present application provides a gelling material slurry, comprising the above-mentioned gelling material and water mixed evenly,
[0032] In one embodiment provided in the present application, the preparation of the gelling material slurry may be performed by uniformly mixing the composite solid raw material, the activator and water.
[0033] In one embodiment provided in the present application, the mixing rate of the gelling material and water is 1500 r / min to 2000 r / min, and the mixing time is 5 min to 6 min.
[0034] In one embodiment provided in the present application, the weight ratio of the fly ash, the blast furnace slag, the steel slag and the silicon slag to the water is 7:1 to 5:1.
[0035] In one embodiment provided in the present application, during the curing process of the gelling material slurry injected into the mold, sealing and curing is required, for example, using a polyethylene film for sealing and curing.
[0036] Compared with the traditional alkali-activated inorganic gelling material preparation technology, the main beneficial effects of this application are as follows:
[0037] (1) The four types of solid waste used in this application are common wastes and by-products in the current energy and smelting industries. They are widely available, cheap and easy to obtain. Through reasonable configuration, they can improve the strength and early strength properties of products prepared from a single raw material, and simultaneously solve the potential environmental hazards caused by the accumulation of multiple solid wastes, providing a way to simultaneously dispose of and resource multiple sources of solid waste.
[0038] (2) The alkali-activated composite inorganic gelling material obtained by the preparation method of the present application can achieve an early maximum unconfined mechanical compressive strength of 107.5 MPa after 7 days of curing by optimizing the types and proportions of raw materials, which is 32.92% higher than that of a single inorganic gelling material. The maximum unconfined mechanical compressive strength can reach 115.8 MPa after 28 days of curing, which is 20.88% higher than that of a single inorganic gelling material.
[0039] (3) The alkali-activated composite inorganic gelling material of the present application has a wide range of raw materials, a simple process flow, no need for high temperature and high pressure processes, low preparation difficulty, easy operation, and is feasible for promotion.
[0040] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be invented and obtained by the schemes described in the description. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.
[0042] Figure 1 These are optical photographs and scanning electron microscope (×5000) images of the four solid waste raw materials involved in this application.
[0043] Figure 2 It is a schematic diagram of the preparation process of the alkali-activated composite inorganic gelled material involved in the present application.
[0044] Figure 3 It is a scanning electron microscope (×5000) image of the alkali-activated composite inorganic gelled material of Examples 1 to 6 of the present application.
[0045] Figure 4 This application relates to the change in compressive strength of the alkali-activated inorganic gelling material prepared based on fly ash, silicon slag and steel slag raw materials.
[0046] Figure 5 This application involves changes in the compressive strength of alkali-activated inorganic gelling materials prepared based on blast furnace slag, silicon slag, steel slag and fly ash raw materials. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application are described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.
[0048] Embodiment 1:
[0049] (1) Selection of solid waste raw materials: Fly ash is fine ash collected from flue gas during the coal-fired process of a thermal power plant in Hebei Province. It is dried at 70°C and sieved to obtain fly ash particles with a particle size of ≤75 μm, with a silicon dioxide content of 43 wt.%, an aluminum oxide content of 40 wt.%, a ferric oxide content of 5.9 wt.%, a calcium oxide content of 2.8 wt.%, and a magnesium oxide content of 0.4 wt.%. Steel slag is from the blast furnace steelmaking process of a steel plant in Hebei Province. It is dried at 70°C, ground and sieved to obtain steel slag particles with a particle size of ≤75 μm, with a silicon dioxide content of 11.6 wt.%, an aluminum oxide content of 4.1 wt.%, a ferric oxide content of 20.0 wt.%, a calcium oxide content of 48.4 wt.%, and a magnesium oxide content of 3.6 wt.%.
[0050] (2) Preparation of composite solid raw material: Fly ash and steel slag powders were selected and combined in a reactor, wherein the weight ratio of fly ash to steel slag was 7:3. The composite solid raw material was obtained by stirring with a mixer for 5 minutes at a stirring speed of 500 r / min.
[0051] (3) Preparation of ultrasonic enhanced composite alkali activator: Weigh an appropriate amount of hydrated sodium silicate solution with a modulus of 3.80, add sodium hydroxide to the solution, adjust Na2O / SiO2 to 0.667, stir thoroughly until completely dissolved, and then oscillate with an ultrasonic oscillator at an ultrasonic power of 500 W, an ultrasonic frequency of 40 kHz, and an ultrasonic time of 3 min until the solution becomes clear and transparent.
[0052] (4) Preparation of alkali-activated inorganic gelling material slurry: The composite solid raw material and the ultrasonic enhanced composite alkali activator were mixed in a weight ratio of 2:1, and an appropriate amount of deionized water was added, and the weight ratio of the deionized water to the composite solid raw material was 1:6. The mixture was stirred in a stirrer for 5 minutes at a stirring speed of 2000 r / min to obtain an alkali-activated inorganic gelling material slurry.
[0053] (5) Material molding and curing: The alkali-activated inorganic gelling material slurry is injected into the mold and shaken until no bubbles emerge. The material and the mold are sealed together with a polyethylene film, and then placed in a constant temperature curing box for curing at 70°C for 12 h. After that, it is taken out and cured at room temperature.
[0054] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained fly ash-steel slag alkali-activated composite inorganic cementitious material test blocks was tested to be 34.2MPa, 24.9MPa and 27.0MPa.
[0055] Embodiment 2:
[0056] (1) Selection of solid waste raw materials: Fly ash was selected in the same manner as in step (1) of Example 1. Silicon slag was a by-product of a silicon refining process at a silicon ore processing plant in Henan Province. The by-product was dried at 70° C. and sieved to obtain silicon slag particles with a particle size of ≤75 μm, with a silicon dioxide content of 97.5 wt.%.
[0057] (2) Preparation of composite solid raw material: Fly ash and silicon slag powders were selected and combined in a reactor, wherein the weight ratio of fly ash to silicon slag was 6:4, and stirred in a stirrer for 5 minutes at a stirring speed of 200 r / min to obtain a composite solid raw material.
[0058] (3) Preparation of ultrasound-enhanced composite alkali activator: the same as step (3) in Example 1.
[0059] (4) Preparation of alkali-activated inorganic gelling material slurry: the same as step (4) in Example 1.
[0060] (5) Material forming and curing: the same as step (5) in Example 1.
[0061] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained fly ash-silicon slag alkali-activated composite inorganic cementitious material test blocks was tested to be 26.8MPa, 31.3MPa and 33.8MPa.
[0062] Embodiment 3:
[0063] (1) Selection of solid waste raw materials: fly ash and steel slag are selected in the same step (1) as in Example 1, and silicon slag is selected in the same step (1) as in Example 2;
[0064] (2) Preparation of composite solid raw materials: Three kinds of powders, namely fly ash, silicon slag and steel slag, were selected and combined in a reactor, wherein the weight ratio of fly ash, silicon slag and steel slag was 6:3:1. The raw materials were stirred in a mixer for 5 minutes at a stirring speed of 200 r / min to obtain a composite solid raw material.
[0065] (3) Preparation of ultrasound-enhanced composite alkali activator: the same as step (3) in Example 1.
[0066] (4) Preparation of alkali-activated inorganic gelling material slurry: the same as step (4) in Example 1.
[0067] (5) Material forming and curing: the same as step (5) in Example 1.
[0068] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained fly ash-silicon slag-steel slag alkali-activated composite inorganic cementitious material test blocks was tested to be 14.4MPa, 16.6MPa and 22.5MPa.
[0069] Embodiment 4:
[0070] (1) Selection of solid waste raw materials: The steel slag is selected in the same manner as step (1) in Example 1. The blast furnace slag comes from the blast furnace steelmaking process of a steel plant in Hebei Province. After being dried at 70° C., it is ground and sieved to obtain slag particles with a particle size of ≤75 μm. The slag particles have a silicon dioxide content of 21.6 wt.%, an aluminum oxide content of 11.4 wt.%, a iron oxide content of 0.6 wt.%, a calcium oxide content of 55.6 wt.%, and a magnesium oxide content of 5.8%.
[0071] (2) Preparation of composite solid raw material: Blast furnace slag and steel slag powders were selected and combined in a reactor, wherein the weight ratio of blast furnace slag to steel slag was 9:1, and stirred in a stirrer for 5 minutes at a stirring speed of 200 r / min to obtain a composite solid raw material.
[0072] (3) Preparation of ultrasound-enhanced composite alkali activator: the same as step (3) in Example 1.
[0073] (4) Preparation of alkali-activated inorganic gelling material slurry: the same as step (4) in Example 1.
[0074] (5) Material forming and curing: the same as step (5) in Example 1.
[0075] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained blast furnace slag-steel slag alkali-activated composite inorganic cementitious material test blocks was tested to be 107.5MPa, 111.1MPa and 115.8MPa.
[0076] Embodiment 5:
[0077] (1) Selection of solid waste raw materials: blast furnace slag is selected from step (1) of Example 4, and fly ash is selected from step (1) of Example 1.
[0078] (2) Preparation of composite solid raw material: Blast furnace slag and fly ash powders were selected and combined in a reactor, wherein the weight ratio of blast furnace slag to fly ash was 8:2, and stirred in a mixer for 5 minutes at a stirring speed of 200 r / min to obtain a composite solid raw material.
[0079] (3) Preparation of ultrasound-enhanced composite alkali activator: the same as step (3) in Example 1.
[0080] (4) Preparation of alkali-activated inorganic gelling material slurry: the same as step (4) in Example 1.
[0081] (5) Material forming and curing: the same as step (5) in Example 1.
[0082] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained blast furnace slag-fly ash alkali-activated composite inorganic cementitious material test blocks was tested to be 96.0MPa, 100.4MPa and 115.7MPa.
[0083] Embodiment 6:
[0084] (1) Selection of solid waste raw materials: blast furnace slag is selected in the same manner as step (1) in Example 4, steel slag is selected in the same manner as step (1) in Example 1, and silicon slag is selected in the same manner as step (1) in Example 2.
[0085] (2) Preparation of composite solid raw materials: Three material powders, namely blast furnace slag, steel slag and silicon slag, were selected and combined in a reactor, wherein the weight ratio of blast furnace slag, steel slag and silicon slag was 7:2:1. The raw materials were stirred in a stirrer for 5 minutes at a stirring speed of 200 r / min to obtain a composite solid raw material.
[0086] (3) Preparation of ultrasound-enhanced composite alkali activator: the same as step (3) in Example 1.
[0087] (4) Preparation of alkali-activated inorganic gelling material slurry: the same as step (4) in Example 1.
[0088] (5) Material forming and curing: the same as step (5) in Example 1.
[0089] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained blast furnace slag-steel slag-silicon slag alkali-activated composite inorganic cementitious material test blocks was tested to be 82.2MPa, 90.8MPa and 99.1MPa.
[0090] Comparative Example 1:
[0091] The difference from Example 1 is that no steel slag is added, and the solid raw materials are all fly ash. Other raw materials and processes are exactly the same as those in Example 1.
[0092] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained single fly ash alkali-activated composite inorganic cementitious material was tested to be 21.8MPa, 19.7MPa and 19.9MPa.
[0093] Comparative Example 2:
[0094] The difference from Example 1 is that fly ash is not added, and the solid raw materials are all steel slag. Other raw materials and processes are exactly the same as those in Example 1.
[0095] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained single steel slag alkali-activated composite inorganic cementitious material was tested to be 7.6MPa, 7.4MPa and 8.4MPa.
[0096] Comparative Example 3:
[0097] The difference from Example 3 is that the weight ratio of fly ash, silicon slag and steel slag is different, and the weight ratio of the three is 6:1:8. Other raw materials and processes are exactly the same as those in Example 3.
[0098] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained fly ash-silicon slag-steel slag alkali-activated composite inorganic cementitious material was tested to be 10.1MPa, 9.6MPa and 9.8MPa.
[0099] Comparative Example 4:
[0100] The difference from Example 4 is that no steel slag is added, and the solid raw materials are all blast furnace slag. Other raw materials and processes are exactly the same as those in Example 4.
[0101] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained single steel slag alkali-activated composite inorganic cementitious material was tested to be 80.9MPa, 93.3MPa and 95.7MPa.
[0102] Comparative Example 5:
[0103] The difference from Example 6 is that the weight ratio of blast furnace slag, silicon slag and steel slag is different, and the weight ratio of the three is 1:1:1. The other raw materials and processes are exactly the same as those in Example 4.
[0104] After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength of the obtained blast furnace slag-steel slag-silicon slag alkali-activated composite inorganic cementitious material was tested to be 49.2MPa, 55.5MPa and 61.1MPa.
[0105] By comparing Example 1 with Comparative Example 1, it can be seen that the fly ash-steel slag composite raw material has higher strength than the alkali-activated inorganic cementitious material prepared from a single fly ash raw material. After 7d, 14d and 28d of curing, its unconfined mechanical compressive strength is increased by 50.34%, 42.95% and 41.88% respectively, and the early strength improvement is more obvious.
[0106] By comparing Examples 1, 3, 5, and 6 with Comparative Example 2, it can be seen that the strength of the alkali-activated inorganic gelling material prepared from a single raw material is lower than that of the composite material. The improvement in the final strength of the product prepared after compounding different raw materials is not due to the effect of a single raw material itself, but mainly depends on the changes in the components after compounding different materials.
[0107] By comparing Example 3 with Comparative Example 3, it can be seen that different ratios of the same raw materials will cause a significant change in the strength of the alkali-activated material, and its final strength can be optimized by adjusting the ratio and type of raw materials.
[0108] By comparing Example 4 with Comparative Example 4, it can be seen that the alkali-activated inorganic cementitious material prepared from the blast furnace slag-steel slag composite raw material has higher strength than that prepared from a single blast furnace slag raw material. After 7d, 14d and 28d of curing, the unconfined mechanical compressive strength is increased by 32.92%, 19.08% and 20.88% respectively. The early strength improvement is also more obvious, which is consistent with the comparison results of Example 4 and Comparative Example 1.
[0109] By comparing Example 5 with Comparative Example 4, it can be seen that the alkali-activated inorganic cementitious material prepared from the blast furnace slag-fly ash composite raw material has higher strength than that prepared from a single blast furnace slag raw material. After 7d, 14d and 28d of curing, its unconfined mechanical compressive strength is increased by 18.71%, 7.58% and 20.85% respectively, and there is also a significant increase in early strength.
[0110] By comparing Example 6 with Comparative Example 5, it can be seen that after the weight ratio of blast furnace slag, silicon slag and steel slag changes, the final material strength decreases significantly. Combined with the results of Comparative Example 4, the strength gap between the alkali-activated inorganic cementitious material prepared from the ternary composite raw material and the single blast furnace slag raw material is quite large. After 7d, 14d and 28d of curing, its unconfined mechanical compressive strength changed by -39.18%, -40.53% and -36.13%, respectively.
[0111] Compared with Examples 1, 2, 3, 6 and Comparative Examples 1 to 5, the unconfined mechanical compressive strength of Examples 4 and 5 after 28 days of curing reached 115.8 MPa and 115.7 MPa respectively, which have significant advantages in structural strength. The strength after compounding different raw materials still exceeds 49.0 MPa, meeting the strength requirements in multiple fields such as building materials, landfill, nuclear waste solidification, and heavy metal solidification.
[0112] By attaching Figure 3 By comparing Examples 1 to 3 with Examples 4 to 6, it can be seen that the generated composite material can effectively fill the pores and cracks generated after the single cementitious material is formed, thereby effectively improving the structural integrity of the material and ensuring the structural strength of the material, which is consistent with the measured compressive strength results.
[0113] From the comparison results of Examples 1 to 6 and Comparative Examples 1 to 5, it can be seen that the strength of the alkali-activated inorganic gelling material prepared from the composite raw material is significantly improved compared with the strength of the single raw material, especially in terms of early strength. However, with the difference in the types and proportions of different raw materials, the strength performance will also decrease significantly. Under the condition of meeting the solid waste disposal needs and strength requirements, the proportions of different raw materials can be optimized and customized to achieve the purpose of optimizing preparation costs and solid waste disposal.
Claims
1. A cementitious material, characterized in that: The cementitious material comprises at least two of fly ash, blast furnace slag, steel slag and silicon slag and an activator: The cementitious material is selected from fly ash and steel slag in a weight ratio of 7:3 to obtain a composite solid raw material; or fly ash and silicon slag in a weight ratio of 6:4 to obtain a composite solid raw material; or blast furnace slag and steel slag in a weight ratio of 9:1 to obtain a composite solid raw material; or blast furnace slag and fly ash in a weight ratio of 8:2 to obtain a composite solid raw material; or blast furnace slag, steel slag and silicon slag in a weight ratio of 7:2:1 to obtain a composite solid raw material; The weight ratio of the composite solid raw material to the activator is 2:1; The fly ash, blast furnace slag, steel slag and silicon slag are dried at 70°C, ground and sieved for collection; The particle sizes of the fly ash, blast furnace slag, steel slag and silicon slag are all no greater than 75 μm; The activator is an alkali activator, and the hydrated silicate solution and the strong alkali are evenly mixed to obtain a clear and transparent activator; The activator is subjected to ultrasonic vibration treatment before use; The modulus of the hydrated silicate solution is 3.8; The strong base is selected from sodium hydroxide, and the molar concentration ratio of Na2O / SiO2 in the activator is 0.667; The preparation method of the cementitious material comprises: uniformly mixing two or three of the fly ash, the blast furnace slag, the steel slag and the silicon slag to obtain a composite solid raw material; uniformly mixing the composite solid raw material and the activator to obtain the cementitious material; The fly ash has a silicon dioxide content of 43wt.%, an aluminum oxide content of 40wt.%, a iron oxide content of 5.9wt.%, a calcium oxide content of 2.8wt.%, and a magnesium oxide content of 0.4wt.%; The steel slag has a silicon dioxide content of 11.6wt.%, an aluminum oxide content of 4.1wt.%, a ferric oxide content of 20.0wt.%, a calcium oxide content of 48.4wt.%, and a magnesium oxide content of 3.6wt.%; The silicon dioxide content in the silicon slag is 97.5wt.%; The blast furnace slag contains 21.6wt.% silicon dioxide, 11.4wt.% aluminum oxide, 0.6wt.% iron oxide, 55.6wt.% calcium oxide and 5.8% magnesium oxide.
2. The cementitious material according to claim 1, characterized in that The ultrasonic power was 500 W, the ultrasonic frequency was 40 kHz, and the ultrasonic time was 3 min.
3. A cementitious material slurry, characterized in that: The method comprises uniformly mixing the gelling material according to any one of claims 1 to 2 and water.
4. The cementitious material slurry according to claim 3, characterized in that: The mixing speed is 2000 r / min and the mixing time is 5 min.
5. The cementitious material slurry according to any one of claims 3 to 4, characterized in that: The weight ratio of deionized water to the composite solid raw material is 1:6.
Citation Information
Patent Citations
Steel slag-based alkali-activated cementing material as well as preparation method and application thereof
CN113045228A
Alkali-activated cementing material doped with steel slag and blast furnace slag
CN113233803A